Room Temperature Terahertz and Frequency Combs Based on Intersubband Quantum Cascade Laser Diodes: History and Future - Manijeh Razeghi; Quanyong Lu (Photonics)
The year 2024 marks the 30-year anniversary of the quantum cascade laser (QCL), which is becoming the leading laser source in the mid-infrared (mid-IR) range. Since the first demonstration, QCL has undergone tremendous development in terms of the output power, wall plug efficiency, spectral coverage, wavelength tunability, and beam quality. Owing to its unique intersubband transition and fast gain features, QCL possesses strong nonlinearities that makes it an ideal platform for nonlinear photonics like terahertz (THz) difference frequency generation and direct frequency comb generation via four-wave mixing when group velocity dispersion is engineered. The feature of broadband, high-power, and low-phase noise of QCL combs is revolutionizing mid-IR spectroscopy and sensing by offering a new tool measuring multi-channel molecules simultaneously in the μs time scale. While THz QCL difference frequency generation is becoming the only semiconductor light source covering 1–5 THz at room temperature. In this paper, we will introduce the latest research from the Center for Quantum Devices at Northwestern University and briefly discuss the history of QCL, recent progress, and future perspective of QCL research, especially for QCL frequency combs, room temperature THz QCL difference frequency generation, and major challenges facing QCL in the future.